2014
DOI: 10.1097/mph.0000000000000042
|View full text |Cite
|
Sign up to set email alerts
|

Azacitidine in the Treatment of Pediatric Therapy-related Myelodysplastic Syndrome After Allogeneic Hematopoietic Stem Cell Transplantation

Abstract: We herein present a case of pediatric therapy-related myelodysplastic syndrome (t-MDS) with complex karyotype who was treated with azacitidine (AZA) for AML1-EVI1 fusion transcript as minimal residual disease after allogeneic hematopoietic stem cell transplantation (HSCT). The patient was started on AZA 41 days after the HSCT without having achieved complete remission. After 9 cycles of AZA, the AML1-EVI1 fusion transcript disappeared, and there was no manifestation of graft versus host disease during AZA trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Table 1 summarizes the publications regarding the use of Aza as salvage treatment for relapse after allo-SCT: until now a total of 601 patients with AML, MDS and other related myeloid malignancies have been published with varying schedules and dosages of Aza. These included 3 prospective, non-randomized trials and the majority of patients reported retrospectively [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Furthermore, Aza was the first treatment of relapse and combined with DLI in some of these patients, while other patients had previously received other salvage therapies or did not receive DLI.…”
Section: Azacitidine For the Treatment Of Relapsementioning
confidence: 99%
“…Table 1 summarizes the publications regarding the use of Aza as salvage treatment for relapse after allo-SCT: until now a total of 601 patients with AML, MDS and other related myeloid malignancies have been published with varying schedules and dosages of Aza. These included 3 prospective, non-randomized trials and the majority of patients reported retrospectively [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25]. Furthermore, Aza was the first treatment of relapse and combined with DLI in some of these patients, while other patients had previously received other salvage therapies or did not receive DLI.…”
Section: Azacitidine For the Treatment Of Relapsementioning
confidence: 99%
“…25 In a single case report, AZA was shown to induce complete remission in a child with treatment-related MDS and signs of early relapse after HSCT, however, long-term follow-up was not reported. 28 The European Working Group of Myelodysplastic Syndromes in Childhood recently reported their experience with AZA in MDS and MDR-AML. 29 Their retrospective analysis comprised a heterogeneous group of children with low-grade MDS (refractory cytopenia of childhood), advanced MDS, secondary MDS, MDR-AML, and relapsed disease after HSCT.…”
Section: Response To Treatment With Azacitidine In Children With Advamentioning
confidence: 99%
“…Together with the experience from the early retrospective reports this prospective trial demonstrated that the combination of Aza and DLI was safe and effective in patients with AML or MDS who relapse after allo-SCT. Overall, as indicated in Table 1, a total of 215 patients with AML, MDS and other related myeloid malignancies had been reported in the literature until 2015 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)23,25). Treatment schedules and dosages of Aza varied between these reports.…”
Section: Aza For the Treatment Of Relapsementioning
confidence: 99%